A comparison of the personality type dimensions of the 1987 Inc. 500 company founders/CEOs with those of slower-growth firms - Ginn, Charles W.; Sexton, Donald L. (Journal of Business Venturing, 1990)
A popular misconception holds that most new businesses experience similar growth stages of start-up, rapid growth, maturity, and decline. Yet, business statistics show that only a small number of firms grow into large organizations. A few experience some growth, but the majority have such small growth that they provide only a marginal income to the founder. While market conditions impact on the growth of the firm, they do not explain growth differences when they occur under similar market conditions. In this paper, the authors have compared psychological type preferences of founders/CEOs of fast-growth firms with those of slow-growth firms under the assumption that differences in psychological preferences, as they relate to gathering, assimilating, and processing information, would have an impact on the strategic or growth orientation of the firm. The results are based on the administration of the Myers-Briggs Type Indicator to the founders/cofounders of 143 firms included in the 1987 Inc. 500 list of the fastest-growing private companies in the United States and the comparison of these results with those of an earlier study of 150 founders/CEOs of successful, yet slower growing firms. The primary personality traits under consideration were an individual's preferred method of gathering information from the environment, making decisions, and drawing conclusions from the information. The results indicate that founders of rapid-growth firms have psychological preferences that are significantly different from those of their slower-growth counterparts. Growth oriented founders prefer an intuitive approach or consideration of future possibilities when gathering information, and a thinking or planned and organized approach to drawing conclusions. These preferences represent those facets most frequently used in strategic or growth planning. Investors in new firms that place importance on the capabilities and orientations of the management team as an evaluation criteria are currently limited to consideration of past experiences. An awareness of the management team's experiences can provide an indication of management ability, but unless their experience involves management of growth, the information related to growth propensities or orientations is limited. A measure of a person's preferences in gathering, assimilating, and processing information can indicate their desires for strategic and/or growth planning. Hence, investors may have another tool that can be used in the investment decision making process. In addition, government policy makers may have the opportunity for increased effectiveness in assistance programs by recognizing that the needs and preferences of founders of rapid-growth companies are significantly different from those of their slower-growing counterparts, and that these differences should be considered in the development of assistance programs.